Effects of habitat loss and human influence on the survival of black-crowned cranes in Africa - Seyoum Kiros Meles; Dessalegn Obsi Gemeda (Brawijaya University, 2019)
This paper reviews the effects of habitat loss and human influence on the survival of Black-crowned cranes in Africa. Black-crowned crane is distributed through Sahel and Sudan Savannah regions of Africa, ranging from the Senegal basin and Guinea-Bissau drainage in West Africa to the western Ethiopian Highlands and south-west Rift Valley in East Africa. Habitat loss, transformation and degradation, and illegal capture and trade for pet industry, are the major threats of the species. Because of habitat loss, the population of Black-crowned cranes is declining across its home range and it is even disappearing in some countries in West Africa. It is predicted that the population decline will continue in the future due to habitat loss and trapping of cranes for domestication. The species is classified as Lower Risk from 1988 to 2000, Near Threatened from 2004 to 2008, and then Vulnerable from 2010 onwards. The rapid conversion of wetlands and intensive land use and different economic development with poor environmental protection threat the survival of Black-crowned cranes. In order to overcome the threats of Black-crowned cranes (Balearica pavonina), habitat conservation and community awareness are essential, not optional.